2019
DOI: 10.1093/treephys/tpz127
|View full text |Cite
|
Sign up to set email alerts
|

Elevated temperature and ozone modify structural characteristics of silver birch (Betula pendula) leaves

Abstract: To study the effects of slightly elevated temperature and ozone (O3) on leaf structural characteristics of silver birch (Betula pendula Roth), saplings of four clonal genotypes of this species were exposed to elevated temperature (ambient air temperature +0.8–1.0 °C) and elevated O3 (1.3–1.4× ambient O3), alone and in combination, in an open-air exposure field over two growing seasons (2007 and 2008). So far, the impacts of moderate elevation of temperature or the combination of elevated temperature and O3 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
8
1
Order By: Relevance
“…The leaf tissue or epidermis thickness has been suggested to control BVOC emissions directly or indirectly by modifying diffusion pathways, residence time of BVOCs within the leaf and within-leaf metabolism ( Hartikainen et al , 2009 ; Niinemets et al , 2014 ; Schollert et al , 2015 ), but we found no statistically significant links between these variables. In this study, we found no connection between trichomes and BVOC emission rates, though trichome condition and number are associated with BVOC emission rates ( Mofikoya et al , 2018 ).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The leaf tissue or epidermis thickness has been suggested to control BVOC emissions directly or indirectly by modifying diffusion pathways, residence time of BVOCs within the leaf and within-leaf metabolism ( Hartikainen et al , 2009 ; Niinemets et al , 2014 ; Schollert et al , 2015 ), but we found no statistically significant links between these variables. In this study, we found no connection between trichomes and BVOC emission rates, though trichome condition and number are associated with BVOC emission rates ( Mofikoya et al , 2018 ).…”
Section: Discussioncontrasting
confidence: 81%
“…Longstreth and Nobel, 1980 ; Jurik et al , 1982 ; Bilkova et al , 2016 ; Kivimäenpää et al , 2016 ; Tian et al , 2016 ). Experimental warming and changes in light intensity have also been shown to cause leaf anatomical alterations in tree species ( Larcher, 2003 ; Luomala et al , 2005 ; Hartikainen et al ., 2009 , 2020 ; Kivimäenpää et al , 2017 ; Thitz et al , 2017 ), as well as in subarctic dwarf shrubs ( Schollert et al ., 2015 , 2017 ). For example, thick epidermis and spongy parenchyma, and a decrease in palisade/spongy parenchyma ratio in connection with warming while thin epidermis, and reduction in glandular trichome (storage structure of terpenoids and other secondary compounds; Loreto and Schnitzler 2010 ) density in connection with shading have been reported for (sub)arctic plant species ( Schollert et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In several tree species, leaf size was positively correlated with the mean annual temperature and/or precipitation [11,53], although the absence of correlation with either latitude or climate had also been reported [54]. The likely reason for the poleward decline in the leaf size of mountain birch is the decrease in ambient temperature, because an experimental temperature elevation increased the leaf size in several birch species [26][27][28][29]. However, the weather conditions did not explain the observed among-year variation in leaf size of mountain birch growing in the central part of the Murmansk region [48], suggesting that other factors than change in temperature [6] may have contributed to the observed pattern.…”
Section: Spatial Variationmentioning
confidence: 99%
“…The experimental studies revealed increases in leaf size in B. pubescens [26,27] and in two other birch species [28,29] in response to elevated ambient temperature. The elevated levels of CO 2 increased the leaf size in B. pubescens [26], but did not induce changes in leaf size in two other birch species [30,31], although the leaf biomass in woody plants generally increased with CO 2 enrichment [2].…”
Section: Introductionmentioning
confidence: 95%
“…Plants are able to acclimate to novel environments over time, and the responses of plant physiological and biochemical traits to short-term versus long-term climatic manipulation may differ from each other (Wang et al, 2019). For example, Hartikainen et al, (2020) showed that the effects of experimental warming on the leaf structure of silver birch (Betula pendula Roth) were more pronounced after the second year of warming, relative to the first. Furthermore, Oksanen and Saleem (1999) found that two growing seasons after the removal of abiotic ozone stress, B. pendula still exhibited ozone-induced growth reduction, suggesting that birch has a long-term biochemical memory.…”
Section: Main Effects Of Warming and Shadingmentioning
confidence: 99%